The mediating effect of the Islamic religious personality on the relationship between the Islamic worldview and intercultural sensitivity among students - Noorfuad, Noorhannah; Wok, Saodah (2018)
Muslims consider themselves to be a ‘family of believers’ (Samovar, 2009) as Islam emphasizes the importance of perceiving and treating other Muslims beyond the differences of appearance and culture. This study examines the relationships of the Islamic worldview and Islamic religious personality with intercultural sensitivity, as well as the mediating effect of the Islamic religious personality on the relationship between the Islamic worldview and intercultural sensitivity in an international learning institution. Religion has an essential role in culture and thus affects our beliefs and behavior. A survey method is used with a questionnaire as the instrument for data collection. A sample of 221 undergraduate students of the International Islamic University of Malaysia (IIUM) participated in the study. The results show that the Islamic worldview and the Islamic religious personality positively influence intercultural sensitivity among Muslim students and that the Islamic religious personality acts as a mediator in the relationship between the Islamic worldview and intercultural sensitivity.